Strategic Internationalization Starts at Home: The Case of Capacity Creation in the Democratic Republic of Congo (DRC) - Lobron, Richard J.; Guillotin, Bertrand; Pietrucha, Martin (Journal of Strategic Innovation and Sustainability, 2019)
The 2016 outbursts of nationalism have left globalization moribund. We wonder how the creation of capacity for transportation infrastructure, leveraging internationalization, affects economic development. We nurture our reflections through the field observations of a US expert whose expertise was requested by DRC leaders. We find that the lack of capacity to perform infrastructure development can be addressed by Western and local institutions, generating greater internationalization. This paper explores the needs of programs and methods through which Western Universities and local organizations can provide such capacity, even in one of the most challenging business environments on Earth.